Inter‐American Court of Human Rights Advisory Opinion OC‐23/17: Jurisdictional, procedural and substantive implications of human rights duties in the context of environmental protection. Issue 2 (17th June 2019) - Abello‐Galvis, Ricardo; Arevalo‐Ramirez, Walter
Abstract : This case note analyses the jurisdictional, procedural and substantive implications of human rights duties in the context of environmental protection as devised by the Inter‐American Court of Human Rights in its Advisory Opinion OC‐23/17 of 15 November 2017 concerning State obligations on the environment, in the context of the rights to life and to personal integrity.